Sleep Disordered Breathing as Measured by SRBD-PSQ and Neurocognition in Children With Hypertension. (20th September 2014) - Lande, Marc B.; Hooper, Stephen R.; Batisky, Donald L.; Kupferman, Juan C.; Szilagyi, Peter G.; Samuels, Joshua A.; Adams, Heather R.
Abstract : BACKGROUND: Cognitive test performance is decreased in hypertensive adults and children, a finding postulated to represent early target-organ damage to the brain. Hypertensive children are often obese, a comorbidity associated with sleep disordered breathing (SDB), itself associated with cognitive problems; potentially confounding the relation between hypertension (HTN) and neurocognition. Our objective was to determine the association between SDB as measured by a scale and questionnaire score and neurocognition among participants enrolled in an ongoing multicenter study of cognition in children with HTN. METHODS: Subjects completed laboratory-based neurocognitive tests. Parents and subjects completed rating scales of executive function, mood, and behavior problems. Parents completed the Sleep-Related Breathing Disorder scale of the Pediatric Sleep Questionnaire (SRBD-PSQ). RESULTS: To date, 38 HTN subjects and 34 control subjects have completed neurocognitive testing and the SRBD-PSQ. Median SRBD-PSQ scores were similar between groups but the HTN group had a higher percentage of subjects with SRBD-PSQ scores in the range suggestive of obstructive sleep apnea (26% vs. 6%, P = 0.03). Overall, higher SRBD-PSQ scores were not significantly associated with worse performance on laboratory-based measures of executive function and other cognitive domains but were significantly associated with worse scores on rating scales of executive function as well as mood and behavior problems. CONCLUSIONS: A larger proportion of children with HTN had scores suggestive of SDB. The results underscore the importance of using a multi-method approach in the assessment of cognition and adjusting for potential confounding effects of SDB in studies of cognition in hypertensive children.